Implementasi Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kantor Camat Bengalon Kabupaten Kutai Timur [Studi Pelayanan Pembuatan Surat Keterangan Penguasaan Tanah (SKPT)] - Ferry Alfarizi; Iman Surya; Muhammad Hairul Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The results of the study show that the implementation of PATEN in the service of making SKPT in the Bengalon District Office has not run optimally. This was obtained based on the results of research through the actions taken by employees who carry out policies in providing services for making SKPT to residents of Bengalon District, as measured using Tangible, Reliability, Responsiveness, Assurance and Empathy dimensions/indicators. Furthermore, there are also several factors that influence the implementation of SKPT preparation services at the Bengalon District Office, namely the awareness factor and the income factor.